Optimal Design and Control Strategy of a Novel 2-DOF Micromanipulator. (13th March 2013) - Li, Yangmin; Wu, Zhigang; Zhao, Xinhua
A kind of novel 2-DOF micromanipulator is designed and analysed based on the two scales of level amplifier principle, which adopts the flexure hinge to replace the traditional hinge. The kinematics, static and dynamic modelling are established, and the input stiffness and actual amplification ratios are calculated. Meanwhile, the finite element analysis (FEA) is applied in order to validate the calculation by using ANSYS software. Then, the theoretical, calculated and simulated values diagrams are compared. Thereafter, the stress and the natural frequency of the stage are also analysed to optimize the platform dimensions. Parasitic motion values are calculated and analysed, and their values are compared in a diagram. The Particle Swarm Optimization (POS) is applied to design and optimize the structure parameters, and finally the optimal structure parameters are obtained and the values of parameters are used by the finite element model (FEM). In addition, a dynamic equation and a suitable control flow chart are designed for the mechanism, and the control strategy is proposed accordingly. Finally, the simulation analysis of the stage control adopting the MATLAB software is performed.